2022
DOI: 10.1093/sleep/zsac238
|View full text |Cite
|
Sign up to set email alerts
|

Dual orexin antagonist normalized sleep homeostatic drive, enhanced GABAergic inhibition, and suppressed seizures after traumatic brain injury

Abstract: Study Objectives Traumatic brain injury (TBI) can result in posttraumatic epilepsy (PTE) and sleep disturbances. We hypothesized that treatment with sleep aids after TBI can ameliorate PTE. Methods CD-1 mice underwent controlled cortical impact (CCI), sham injury or no craniotomy. Sham and CCI groups underwent a month-long daily treatment with sleep aids including a dual orexin antagonist (DORA-22) or THIP (gaboxadol) or a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In addition, orexin, another focus of this study, is secreted by a group of neurons in the hypothalamus that are located closest to the STN and project to the STN and SNr (Peyron et al, 1998). Several studies have found that the orexin pathway plays a vital role in various seizures (Samzadeh et al, 2020;Celli and Luijtelaar, 2022;Konduru et al, 2022). Previous studies have observed the expression and co-localization of OX1R and OX2R in the STN and SNr (Korotkova et al, 2002;Li et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, orexin, another focus of this study, is secreted by a group of neurons in the hypothalamus that are located closest to the STN and project to the STN and SNr (Peyron et al, 1998). Several studies have found that the orexin pathway plays a vital role in various seizures (Samzadeh et al, 2020;Celli and Luijtelaar, 2022;Konduru et al, 2022). Previous studies have observed the expression and co-localization of OX1R and OX2R in the STN and SNr (Korotkova et al, 2002;Li et al, 2019).…”
Section: Discussionmentioning
confidence: 96%
“…After CCI, mice have identifiable gliosis and changes in sleep and EEG delta power ( Willie et al, 2012 ; Hazra et al, 2014 ; Thomasy et al, 2017 ; Thomasy and Opp, 2019 ; Konduru et al, 2021 , 2022 ). Another study found that EEG delta power during NREM sleep decreased by 55% after CCI at 7 days post-injury, and theta power (5.5–8.5 Hz) increased 59% during REM sleep.…”
Section: Models Of Tbi and Sleep Disturbancesmentioning
confidence: 99%